Factors Related to Nurses Compliance in Hand Hygiene Businesses in Kudungga District of East Kutai - Rahmawati Rahmawati; Hilda Hilda; Diah Setiani (International Journal of Global Sustainable Research, 2023)
In an effort to reduce the incidence of HAIs, hand hygiene is very important because nurses always interact directly with the patient and the patient's environment. The objective is to analyze the factors related to the compliance of nurses in the implementation of hand hygiene in the hospital room of RSUD Kudungga district of Eastern Kutai in 2023. This research method is a type of quantitative researcher with analytical studies and with cross sectional design. In this study, the sampling technique used is Non-probobality sampler with purposive sampler. There are several factors in the implementation of hand-hygiene where these factors are facility factors, reward and punishment, compliance, attitude, knowledge and role of the PPI Team influence on the execution of hand hygiene to be maximum especially in Mutiara RSUD Kudungga district east quarter in 2023.